2015
DOI: 10.25026/jsk.v1i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Efek Ekstrak Tanduk Rusa Sambar (Cervus unicolor) Terhadap Kadar Ureum Dan Kreatinin Tikus Putih (Rattus novergicus)

Abstract: ABSTRAKTelah dilakukan penelitian yang bertujuan untuk menguji keamanan penggunaan ekstrak tanduk rusa sambar (Cervus unicolor) ditinjau dari dosis dan lama pemberian dengan mengukur kadar ureum dan kreatinin dalam darah tikus putih (Rattusnovergicus). Tikus sebanyak 9 ekor dibagi menjadi 3 kelompok yaitu kelompok 1 sebagai kontrol, kelompok 2 perlakuan dosis I dan kelompok 3 perlakuan dosis II. Kelompok kontrol diberi pakan standar dan air suling, Kelompok 2 diberi pakan standar dan dosis sebanyak 1,55 mg/200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Post Hoc continued the results of the Post Hoc follow-up test showed that the negative control, positive control, dose of 150 mg/kg BW, dose of 200 mg/kg BW and 250 mg/kg BW were significantly different from the normal group, meaning that the test animals in the treatment group were in a different condition. sick or experiencing an increase in creatinine levels caused by streptozotocin induction, causing hyperglycemia which can increase ROS production as a result, oxidative stress will occur so that it can disrupt the glomerular filtration rate and can reduce the function of renal filtration which causes creatinine levels in the blood to increase [15].…”
Section: Resultsmentioning
confidence: 99%
“…Post Hoc continued the results of the Post Hoc follow-up test showed that the negative control, positive control, dose of 150 mg/kg BW, dose of 200 mg/kg BW and 250 mg/kg BW were significantly different from the normal group, meaning that the test animals in the treatment group were in a different condition. sick or experiencing an increase in creatinine levels caused by streptozotocin induction, causing hyperglycemia which can increase ROS production as a result, oxidative stress will occur so that it can disrupt the glomerular filtration rate and can reduce the function of renal filtration which causes creatinine levels in the blood to increase [15].…”
Section: Resultsmentioning
confidence: 99%
“…Jumlah ulangan pada penelitian ini dilakukan berdasarkan jumlah minimum pengulangan (Defriana et al, 2015).…”
Section: Metodeunclassified
“…2 Ginjal membuang banyak toksin dan zat asing lainnya yang diproduksi oleh tubuh atau pencernaan, seperti pestisida, makanan, dan obat-obatan. 3 Salah satu obat yang dapat merusak ginjal yaitu antibiotik golongan aminoglikosida, seperti misalnya gentamisin. Gentamisin merupakan antibiotik yang umum digunakan dalam pengobatan infeksi yang mengancam jiwa 4,5 dan memiliki spektrum luas yang bersifat nefrotoksik terhadap manusia dan hewan.…”
Section: Pendahuluanunclassified